MODEL SMART SELLING TECHNOLOGY DALAM PENGELOLAAN PRODUK HILIR PETANI, NELAYAN DAN INDUSTRI KREATIF MASYARAKAT DESA UNTUK MEWUJUDKAN UMKM/IKM GO GLOBAL PADA DESA SIRUKKUNGON - Beatrice Nathania; Andi Setiawan; Erikson Damanik (Politeknik Bisnis Indonesia, 2023)
The urgency of this research is to build a Smart selling Technology model in Sirukkungon Village MSMEs/IKMs. In the current digital era, MSMEs/IKMs should apply technology in processing their downstream products, but in reality Sirukkungon Village MSMEs/IKMs have still not adopted technology. This is due to the lack of human resources who understand technology. Through this Smart selling Technology Model, all MSME/IKM players, including farmers, fishermen and creative industries, get a technology-based downstream product management platform so that the products they produce can be sold across provinces and even the world. In addition, the business world will be equipped with knowledge about business management. intelligent targeting downstream products that have high selling power so that the system to be built can really be utilized optimally. The aim of this research is to produce a smart, online-based and integrated sales system technology plan/model to manage downstream products for farmers, fishermen and creative industries in Sirukkungon Village to realize MSMEs/IKM Go Global. With the model that will be built, agricultural, fishery and community creative industry products can be managed optimally and have high selling quality. The analytical method used is qualitative analysis and design. The results of this research are a system design and strategy for the Smart selling Technology Model in Managing the Downstream Products of Farmers, Information Fishermen and Creative Industries in the form of a sales system designed to be web-based and can be used for the sales process of products produced by the community's creative economy.